Seed-layer effect on highly oriented ZnO nanorod array fabrication - Zhou,FC; Yuan,L; Feng,SH; McLachlan,MA; Zhang,JQ (Chinese Journal of Inorganic Chemistry, 2018)
© 2018, Chinese Chemical Society. All Rights Reserved. Vertically aligned ZnO nanorod arrays have been extensively applied to the fabrication of various optoelectronic devices owing to their versatile properties. However, to control and investigate the morphology of nanorods is directly related to device performances. A seeded substrate is favourable for the hydrothermal synthesis of nanorods by lowering the nucleation barrier and restricting the migration of the disordered nucleation. Therefore, varying the seed layer properties is a feasible and effective way to control the nanorod growth. In this paper, three different methods sol-gel, spray pyrolysis and pulse laser deposition (PLD) were employed to the ZnO seed layer preparation. For each preparation method, the crystal structure, morphologies, surface roughness and properties of ZnO seed layers were characterised by X-ray diffraction (XRD), scanning electron microscopy (SEM) and atomic force microscopy (AFM), respectively. ZnO nanorod arrays with different structures and morphological properties were synthesised on the prepared seed layers by hydrothermal treatment. The ZnO nanorods exhibit strong substrate-dependent properties. Combined with the characteristics of ZnO seed layers, the difference of growth mechanisms for each method is proposed by analyzing the nanorod properties on the seed layers.